DYNAMIC CORRELATION BETWEEN SELECTED CEREALS TRADED IN COMMODITY EXCHANGE MARKET IN AP VOJVODINA - Živkov, Dejan; Stankov, Biljana; Roganović, Milijana; Momčilović, Mirela (Economics of Agriculture, 2022)
This paper investigates the level of pairwise dynamic correlations between prices of four agricultural commodities – corn, wheat soybean and barley that are traded in Novi Sad commodity exchange market. We use DCC-GARCH model, which is specially designed for this type or research. The results of the estimated dynamic conditional correlations show that low and positive correlation exist between all the pairs of the selected agricultural commodities, where the highest correlation is recorded between wheat and barley (24%), corn-barley pair follows (20%), while all other dynamic correlations are below 20%. The results indicate that price movements of the selected agricultural cereals are independent, which means that price discovery of one agricultural commodity does not provide information about the price of another agricultural commodity. Therefore, our results strongly suggest that traders in this market do not rely on the price co-movements between particular agricultural assets when they plan their selling or buying strategies, but to analyze fundamental macroeconomic factors.